Psychological Capital: A Bridge between Openness to Experience and Teacher Effectiveness during Distance Learning - Yunandar, Annisa Nabila Ramadhani; Salim, Rose Mini Agoes; Safitri, Shahnaz (Psychological Research on Urban Society, 2023)
Distance learning as an impact of COVID-19 pandemic becomes a challenge for teacher effectiveness. The current study examined the role of psychological capital as a mediator of the relationship between openness to experience and teacher effectiveness. This study involved 172 senior high school teachers in Jabodetabek as respondents who are currently conducting distance learning. Respondents are 117 female teachers (68%) and 55 male teachers (32%) who have teaching experience in the range of 5 months to 35 years (M = 161.34, SD = 121.8). The mediation analysis results revealed a significant indirect effect between openness to experience and teacher effectiveness through psychological capital, ? = .999, p < .01, 95% CI [.668, 1.369]. These findings prove that psychological capital mediates the relationship between openness to experience and teacher effectiveness. Therefore, teachers should have high openness to experience to increase psychological capital so teacher effectiveness will also increase.